Comparative study of hole quality performance in drilling of CFRP/Al7075-T6 stack using tetrahedral amorphous carbon coated drill - Joy Mathavan, J.; Hafiz Bin Hassan, M.; Samad Bin Mahmud, A. (AIP Publishing, 2022)
Stack up materials which consists of fiber composite panel and aluminium / titanium alloys keep on replacing conventional materials in the aircraft industry. Though stack up materials have enhanced mechanical properties, machining of it is still being as a challenge. This paper compares the hole quality of the holes drilled by uncoated and tetrahedral amorphous carbon (Ta-C) coated tungsten carbide twist drills in terms of hole diameter error, circularity error and hole surface roughness. Drilling experiments were performed at a constant speed of 2600 rev/min and feed rate of 0.05 mm/rev. The stack material of Al7075-T6/CFRP which has a composite laminate thickness of 3.387 mm and Al7075-T6 thickness of 3.317 mm was used as workpiece and drilled under single shot process in dry condition. The results show that, uncoated drill produces better stack up diameter tolerance, circularity and Al7075-T6 surface finish, while Ta-C coated drill bits produce better CFRP surface finish.